Review—Characterization of Metal-Contamination Effects in Silicon. (1st January 2016) - Polignano, M. L.; Codegoni, D.; Galbiati, A.; Grasso, S.; Mica, I.; Moccia, G.; Nardone, G.; Russo, F.
Abstract : Various measurement techniques are compared and the most suitable methods for contamination detection are identified. The results of this study show that it is not possible to define a unique recipe that can be applied in all cases. Concerning metal contaminants, the stratigraphic in-depth distribution and hence the diffusivity of contaminants determines the most effective approach. Iron and palladium are chosen as the examples of fast diffusers, molybdenum and tungsten as slow diffusers. Fast diffusers like iron and palladium diffuse through several hundred microns during an ordinary thermal treatment. Minority carrier lifetime measurements are probably the best choice to detect these contaminants. Molybdenum and tungsten do not diffuse deep enough to be efficiently revealed by recombination lifetime measurements, but are easily revealed in the silicon volume by DLTS. Because of their low diffusivity, a very small amount of these elements per unit surface may result in a significant concentration in the near-surface region where devices are built. Ion implantation is confirmed to be an important source of metal contamination. It is shown that ion implantation can be responsible both for iron contamination and for contamination by slow diffusers, such as molybdenum and tungsten. A procedure for monitoring molybdenum and tungsten contamination in ion implantation processes by DLTS is defined and calibrated. Finally, the efficiency of some gettering techniques in reducing iron, molybdenum and tungsten contamination is discussed. Gettering is found to be active at relatively high contaminant concentrations, but low contamination levels are not gettered under our experimental conditions. Carbon implantation showed partial efficiency in gettering molybdenum and tungsten, whereas gettering did not take place after silicon implantation.